Approach to More Efficient Design of Hybrid Components - Hielscher, Christian; Grenz, Julian; Camberg, Alan Adam; Wingenbach, Nils (ATZ worldwide)

Cooperative Verification via Collective Invariant Generation - Haltermann, Jan Frederik; Wehrheim, Heike (arXiv:2008.04551)
Software verification has recently made enormous progress due to the development of novel verification methods and the speed-up of supporting technologies like SMT solving. To keep software verification tools up to date with these advances, tool developers keep on integrating newly designed methods into their tools, almost exclusively by re-implementing the method within their own framework. While this allows for a conceptual re-use of methods, it requires novel implementations for every new technique. In this paper, we employ cooperative verification in order to avoid reimplementation and enable usage of novel tools as black-box components in verification. Specifically, cooperation is employed for the core ingredient of software verification which is invariant generation. Finding an adequate loop invariant is key to the success of a verification run. Our framework named CoVerCIG allows a master verification tool to delegate the task of invariant generation to one or several specialized helper invariant generators. Their results are then utilized within the verification run of the master verifier, allowing in particular for crosschecking the validity of the invariant. We experimentally evaluate our framework on an instance with two masters and three different invariant generators using a number of benchmarks from SV-COMP 2020. The experiments show that the use of CoVerCIG can increase the number of correctly verified tasks without increasing the used resources

Structural Information and Communication Complexity - 27th International Colloquium, SIROCCO 2020, Paderborn, Germany, June 29 - July 1, 2020, Proceedings

SPAA '20: 32nd ACM Symposium on Parallelism in Algorithms and Architectures, Virtual Event, USA, July 15-17, 2020

SEMANTIC TAGGING OF REQUIREMENT DESCRIPTIONS: A TRANSFORMER-BASED APPROACH - Kersting, Joschka; Bäumer, Frederik Simon (PROCEEDINGS OF THE INTERNATIONAL CONFERENCE ON APPLIED COMPUTING 2020)
Keywords: Software Requirements; Natural Language Processing; Transfer Learning; On-The-Fly Computing

Einleitung – Introduction - Seng, Eva- Maria; Göttmann, Frank (Innovation in der Bauwirtschaft – Innovation in the building industry. Wesersandstein vom 16. bis 19. Jahrhundert – Weser Sandstone form the 16th to the 19th Century)

Die Wiedereinrichtung der Bauhütten in Europa im 19. und 20. Jahrhundert - Seng, Eva- Maria; Silvestri, Marco (LE CHANTIER CATHÉDRAL EN EUROPE diffusion et sauvegarde des savoirs, savoir-faire et matériaux du Moyen Âge à nos jours)

Kandidatur zum Bauhüttenwesen Die internationale für das immaterielle Kulturerbe der UNESCO - Seng, Eva- Maria (Europäische Bauhütten – Immaterielles Kulturerbe der Menschheit)

Opportunities of 3D Machine Learning for Manufacturability Analysis and Component Recognition in the Additive Manufacturing Process Chain - Nickchen, Tobias; Engels, Gregor; Lohn, Johannes (Industrializing Additive Manufacturing)

Die Ulmer Münsterbauhütte - Seng, Eva- Maria; Hilbert, Michael (Europäische Bauhütten – Immaterielles Kulturerbe der Menschheit)

Pall Mall. From the sportsground to the urban pleasure ground - Seng, Eva- Maria (Vortrag am 17.09.2016 auf dem 34. Weltkongreß für Kunstgeschichte (CIHA) in Beijing)

Recombination mechanisms of luminescence type gas sensors - Poeplau, Michael; Ester, Stephan; Henning, Bernd; Wagner, Thorsten (Physical Chemistry Chemical Physics)
The impact of the recombination mechanisms in luminescent materials is discussed with regard to luminescence based gas-sensing applications and the use of semiconducting materials, as an alternative to organic–metal complexes, is outlined.

In-depth Analysis of the Effects of Smart Services on Value Creation - Reinhold, Jannik; Frank, Maximilian; Koldewey, Christian; Dumitrescu, Roman; Buss, Eugen (Proceedings of the ISPIM Connects Bangkok – Partnering for an Innovative Community)

Terror attacks and individual investor behavior: Evidence from the 2015–2017 European terror attacks - Hasso, Tim; Pelster, Matthias; Breitmayer, Bastian (Journal of Behavioral and Experimental Finance)

Vormärz-Handbuch

„Romantik“ und „Vormärz“. Ein Streitfall - Eke, Norbert Otto (Georg Büchner und die Romantik)

Ethische Erinnerungskultur. Peter Weiss‘ Memorial des ‚ganzen‘ Widerstands - Eke, Norbert Otto (Peter Weiss erinnernd – Ansichten und Einsichten)

Vormärz – Prolegomenon einer Epochendarstellung - Eke, Norbert Otto (Vormärz-Handbuch)

Vormärz und Klassik - Eke, Norbert Otto (Vormärz-Handbuch)

Vormärz und Aufklärung - Eke, Norbert Otto (Vormärz-Handbuch)

Exil - Eke, Norbert Otto (Vormärz-Handbuch)

Habitueller Antiklassizismus. Christian Dietrich Grabbe und die Kritik an Klassik und Romantik im Vormärz - Eke, Norbert Otto (Zwischen Emanzipation und Sozialdisziplinierung: Pädagogik im Vormärz)

Nachruf: Hartmut Steinecke zum Gedenken - Eke, Norbert Otto (Zeitschrift für deutsche Philologie)

Der ‚Eigene Kalender‘ des Erinnerns: Die Wahrheit der erfundenen Erinnerung in Herta Müllers Romanen, Erzählungen und Essays - Eke, Norbert Otto (German Life and Letters (Special Issue: Herta Müller and the Currents of European History))

Auslegungsmethode für zyklisch beanspruchte Stahl/CFK-Klebverbindungen unter besonderer Berücksichtigung des Rissfortschritts - Kowatz, Jannik; Teutenberg, Dominik; Meschut, Gerson (20. Kolloquium Gemeinsame Forschung in der Klebtechnik)

CFD-basierte Untersuchung von Zweiphasenströmungen in strukturierten Packungen - Bertling, René; Hack, Mathias; Ausner, Ilja; Kenig, Eugeny

CFD-Simulationen von Film- und Rinnsalströmungen auf mikrostrukturierten Oberflächen - Bertling, René; Hack, Mathias; Ausner, Ilja; Kenig, Eugeny

Dynamische Simulation von industriellen Kreislaufprozessen zur Vermeidung von Notfallsituationen bei der chemischen Absorption - Bothe, Mike; Fedorov, A.; Frei, H.; Lutters, N.; Kenig, E. Y. (Chemie Ingenieur Technik)

Semi-automatized consistency assessment in Scenario-Technique: Generic consistency patterns and user types - Gräßler, Iris; Scholle, Philipp; Thiele, Henrik (ISPIM Conference Proceedings)

Automatisierte Identifikation und Charakterisierung von Anforderungsabhängigkeiten – Literaturstudie zum Vergleich von Lösungsansätzen - Gräßler, Iris; Preuß, Daniel; Oleff, Christian (Proceedings of the 31st Symposium Design for X (DFX2020); 16. - 18. Sep. 2020)

Which future do we want? It's up to us! - 4 future scenarios for automation 2030 - Gräßler, Iris; Bettenhausen, Kurt D.; Bilgic, Attila M.; Dirzus, Dagmar (at-Automatisierungstechnik 68(6))

The new V-Model of 2206 and its validation - Gräßler, Iris; Hentze, Julian (at-Automatisierungstechnik 68(5))

Scenario Technique - Gräßler, Iris; Scholle, Philipp; Thiele, Henrik (Integrated Design Engineering. Interdisciplinary and Holistic Product Development)

7. Workshop Mensch-Maschine-Interaktion in sicherheitskritischen Systemen - Mentler, Tilo; Reuter, Christian; Nestler, Simon; Kaufhold, Marc-Andre; Herczeg, Michael; Pottebaum, Jens (Mensch und Computer 2020 - Workshopband)

Method for Systematic Assessment of Requirement Change Risk in Industrial Practice - Gräßler, Iris; Oleff, Christian; Scholle, Philipp (Applied Sciences 23/2020 (23))

Automation 2030. Zukunft gestalten - Szenarien und Empfehlungen - Gräßler, Iris; Thiele, Henrik; al., et.

Digitaler Zwilling - WiGeP Positionspapier - Stark, Rainer; Thoben, Klaus-Dieter; Gerhard, Detlef; Hick, Hannes; Kirchner, Eckhard; Anderl, Reiner; Wartzack, Sandro; Krause, Frank-Lothar; Gräßler, Iris; Pottebaum, Jens; Schleich, Benjamin; Stelzer, Ralph; et al.

GIWAXS-SIIRkit: scattering intensity, indexing and refraction calculation toolkit for grazing-incidence wide-angle X-ray scattering of organic materials - Savikhin, Victoria; Steinrück, Hans-Georg; Liang, Ru-Ze; Collins, Brian A.; Oosterhout, Stefan D.; Beaujuge, Pierre M.; Toney, Michael F. (Journal of Applied Crystallography)
Grazing-incidence wide-angle X-ray scattering (GIWAXS) has become an increasingly popular technique for quantitative structural characterization and comparison of thin films. For this purpose, accurate intensity normalization and peak position determination are crucial. At present, few tools exist to estimate the uncertainties of these measurements. Here, a simulation package is introduced called GIWAXS-SIIRkit , where SIIR stands for scattering intensity, indexing and refraction. The package contains several tools that are freely available for download and can be executed in MATLAB. The package includes three functionalities: estimation of the relative scattering intensity and the corresponding uncertainty based on experimental setup and sample dimensions; extraction and indexing of peak positions to approximate the crystal structure of organic materials starting from calibrated GIWAXS patterns; and analysis of the effects of refraction on peak positions. Each tool is based on a graphical user interface and designed to have a short learning curve. A user guide is provided with detailed usage instruction, tips for adding functionality and customization, and exemplary files.

Crystallization and Organic Field‐Effect Transistor Performance of a Hydrogen‐Bonded Quaterthiophene - Gebers, Jan; Özen, Bilal; Hartmann, Lucia; Schaer, Michel; Suàrez, Stéphane; Bugnon, Philippe; Scopelliti, Rosario; Steinrück, Hans-Georg; Konovalov, Oleg; Magerl, Andreas; Brinkmann, Martin; Petraglia, Riccardo; et al. (Chemistry – A European Journal)

Impact of Processing on Structural and Compositional Evolution in Mixed Metal Halide Perovskites during Film Formation - Abdelsamie, Maged; Xu, Junwei; Bruening, Karsten; Tassone, Christopher J.; Steinrück, Hans-Georg; Toney, Michael F. (Advanced Functional Materials)

Heterogeneous Behavior of Lithium Plating during Extreme Fast Charging - Tanim, Tanvir R.; Paul, Partha P.; Thampy, Vivek; Cao, Chuntian; Steinrück, Hans-Georg; Nelson Weker, Johanna; Toney, Michael F.; Dufek, Eric J.; Evans, Michael C.; Jansen, Andrew N.; Polzin, Bryant J.; Dunlop, Alison R.; et al. (Cell Reports Physical Science)

Advanced Characterization in Clean Water Technologies - Bone, Sharon E.; Steinrück, Hans-Georg; Toney, Michael F. (Joule)

Understanding additive controlled lithium morphology in lithium metal batteries - Kasse, Robert M.; Geise, Natalie R.; Ko, Jesse S.; Nelson Weker, Johanna; Steinrück, Hans-Georg; Toney, Michael F. (Journal of Materials Chemistry A)
Investigation of the mechanisms underlying control of electrodeposited lithium metal morphology using electrolyte additives in lithium metal batteries.

Time‐Resolved Structural Kinetics of an Organic Mixed Ionic–Electronic Conductor - Paulsen, Bryan D.; Wu, Ruiheng; Takacs, Christopher J.; Steinrück, Hans-Georg; Strzalka, Joseph; Zhang, Qingteng; Toney, Michael F.; Rivnay, Jonathan (Advanced Materials)

Interfacial Speciation Determines Interfacial Chemistry: X‐ray‐Induced Lithium Fluoride Formation from Water‐in‐salt Electrolytes on Solid Surfaces - Steinrück, Hans-Georg; Cao, Chuntian; Lukatskaya, Maria R.; Takacs, Christopher J.; Wan, Gang; Mackanic, David G.; Tsao, Yuchi; Zhao, Jingbo; Helms, Brett A.; Xu, Kang; Borodin, Oleg; Wishart, James F.; et al. (Angewandte Chemie International Edition)

Concentration and velocity profiles in a polymeric lithium-ion battery electrolyte - Steinrück, Hans-Georg; Takacs, Christopher J.; Kim, Hong-Keun; Mackanic, David G.; Holladay, Benjamin; Cao, Chuntian; Narayanan, Suresh; Dufresne, Eric M.; Chushkin, Yuriy; Ruta, Beatrice; Zontone, Federico; Will, Johannes; et al. (Energy & Environmental Science)
Direct measurements of concentration and velocity profiles in a polymeric lithium-ion battery electrolyte provide insights into the transference number.

Interface between Water–Solvent Mixtures and a Hydrophobic Surface - Prihoda, Annemarie; Will, Johannes; Duchstein, Patrick; Becit, Bahanur; Lossin, Felix; Schindler, Torben; Berlinghof, Marvin; Steinrück, Hans-Georg; Bertram, Florian; Zahn, Dirk; Unruh, Tobias (Langmuir)

Tortuosity Effects in Lithium-Metal Host Anodes - Chen, Hao; Pei, Allen; Wan, Jiayu; Lin, Dingchang; Vilá, Rafael; Wang, Hongxia; Mackanic, David; Steinrück, Hans-Georg; Huang, William; Li, Yuzhang; Yang, Ankun; Xie, Jin; et al. (Joule)

Toward quantifying capacity losses due to solid electrolyte interphase evolution in silicon thin film batteries - Steinrück, Hans-Georg; Cao, Chuntian; Veith, Gabriel M.; Toney, Michael F. (The Journal of Chemical Physics)

Selbstbau eines digitalen Low-Cost-Fotometers für den Chemieunterricht - Witte, Thomas; Hanemann, Stefan; Sommerfeld, Herbert; Temmen, Katrin; Fechner, Sabine (CHEMKON)